A multiagent educational resources retrieval platform driven by cultural aspects - Bender, Cristina (2006)
In this work we propose a multiagent architecture for webb educational resouces retrieval that helps users to find courses according to their personal and cultural aspects. Cultural aspects aree preferences and ways of behavior determined by the person's culture. In this work, the cultural aspects are just the features that distinguish between the preferences of users from diferet regions. This multiagent platform includes several kinds of agents with different functionalities. We particularly model the Educational Resources Finder Agent as a Graded BDI Agent, which is in charged of a felxible retrieval od the best courses according to the student profile. We outline the overall multiagent system and present an example illustrarting the searching process.